Analysis of French Orthographic Errors Among Students at a Vocational School in Yogyakarta - Tanjung S, Angela; Tobing, Roswita Lumban; Gultom, Aryadi Manuel (PT FORMOSA CENDEKIA GLOBAL, 2024)
There are some elements of French orthography and mastering them is essential for proper writing and communication in the French language. This study aims to analyze French orthographic errors in essays written by students at a vocational school in Yogyakarta, where French is taught as a foreign language. The research focuses on errors related to self-introduction essays, covering aspects such as name, age, profession, address, nationality, and hobbies. Data collection involved students writing mini-essays about themselves, with errors noted during the process. The analysis followed language error theory, detailing error types, frequency, and patterns. Results revealed syntactic level errors among 30 participants, with 56 orthographic errors identified. The errors encompassed accents (é, è), apostrophes, capitalization, conjugation, and miscellaneous errors. These findings shed light on common challenges faced by beginner French learners, providing valuable insights for language teaching and curriculum development at vocational